The WiggleZ Dark Energy Survey: measuring the cosmic growth rate with the two-point galaxy correlation function - Contreras, C.; Blake, C.; Poole, G. B.; Marin, F.; Brough, S.; Colless, M.; Couch, W.; Croom, S.; Croton, D.; Davis, T. M.; Drinkwater, M. J.; Forster, K.; et al. (Monthly Notices of the Royal Astronomical Society, 2013)
The growth history of large-scale structure in the Universe is a powerful probe of the cosmological model, including the nature of dark energy. We study the growth rate of cosmic structure to redshift z = 0.9 using more than 162 000 galaxy redshifts from the WiggleZ Dark Energy Survey. We divide the data into four redshift slices with effective redshifts z = [0.2, 0.4, 0.6, 0.76] and in each of the samples measure and model the two-point galaxy correlation function in parallel and transverse directions to the line of sight. After simultaneously fitting for the galaxy bias factor we recover values for the cosmic growth rate which are consistent with our assumed Λcold dark matter (ΛCDM) input cosmological model, with an accuracy of around 20 per cent in each redshift slice. We investigate the sensitivity of our results to the details of the assumed model and the range of physical scales fitted, making close comparison with a set of N-body simulations for calibration. Our measurements are consistent with an independent power-spectrum analysis of a similar data set, demonstrating that the results are not driven by systematic errors. We determine the pairwise velocity dispersion of the sample in a non-parametric manner, showing that it systematically increases with decreasing redshift, and investigate the Alcock-Paczynski effects of changing the assumed fiducial model on the results. Our techniques should prove useful for current and future galaxy surveys mapping the growth rate of structure using the two-dimensional correlation function. © 2013 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.
Keywords: Surveys; Cosmological parameters; Large-scale structure of universe